2021
DOI: 10.20960/nh.03405
|View full text |Cite
|
Sign up to set email alerts
|

Immunonutrition in fast-track surgical patients — evidence review and adapted algorithm

Abstract: Inmunonutrición del paciente quirúrgico en los procedimientos fast-track: revisión de la evidencia y algoritmo adaptado Immunonutrition in fast-track surgical patients -evidence review and adapted algorithm 10.20960/nh.03405 RV 3405 Inmunonutrición del paciente quirúrgico en los procedimientos fast-track: revisión de la evidencia y algoritmo adaptado Immunonutrition in fast-track surgical patients -evidence review and adapted algorithm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
2
0
3
Order By: Relevance
“…The increase in evidence regarding the use of these formulas for this type of patients has resulted in clinical guidelines recommending their use in upper digestive tract surgery [ 2 ]. Nevertheless, their use in an ERAS protocol is not yet fully recommended due to a lack of evidence in studies that included these protocols [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in evidence regarding the use of these formulas for this type of patients has resulted in clinical guidelines recommending their use in upper digestive tract surgery [ 2 ]. Nevertheless, their use in an ERAS protocol is not yet fully recommended due to a lack of evidence in studies that included these protocols [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients reported in the case reports were previously healthy, including 3 adult women and 7-year-olds. In contrast, the reported patient’s immunity level was low at the time of hospitalization after cardiac surgery, which might be due to cardiac surgery injury, CPB, blood loss and malnutrition ( Angele and Faist, 2002 ; Gaudriot et al., 2015 ; Candela et al., 2021 ). A previous study showed that the bactericidal activity of neutrophil bactericidal agents against Staphylococcus aureus was decreased after cardiac surgery ( Mekontso-Dessap et al., 2005 ).…”
Section: Discussionmentioning
confidence: 92%
“…Adaptada de Gómez Candela C et al (2021) (25) Sobre los posibles efectos benéficos de la inmunonutrición en las patologías oncológicas se investiga desde hace 30 años. No obstante, es a partir del año 2000 cuando se ha intensificado la actividad investigativa.…”
Section: Nucleótidosunclassified